TINJAUAN KOGNISI DESAIN PRODUK KEMASAN SEBAGAI UNSUR IDENTITAS BUDAYA POPULER ATAS PRODUK KEMASAN MAKANAN INDUSTRI KECIL MENENGAH (IKM) - Hidayat, Moch. Junaidi (Jurnal Kawistara, 2011)
Packaging is a media for producer and costomer to communicate the message through informative communication.The problem of packaging design will appear by the time of delivering the message in the form of sign, that car be considered as the game of cognition aspect. The expression of packaging sign is not only in the form of visual (text, image, color and other graphic aspects) but also in, material up to the function of packaging as symbolization of cultural development of the packaging design.This paper is a preliminary research result trying to identify, describe and prove the phenomena of design relationship between customer and packaging its and its effect to packaging production by Medium â Small Scale Industry (IKM), at the same time as the conceptual idea to improve the design object of food packaging of MediumSmall Scale Industry (IKM) in East Java based on Media-Cultural Study. The position of Medium â Small Scale Industry (IKM) becomes interesting because of the typical value of production consumption process of Medium â Small Scale Industry (IKM) compared to the fabrication scale is becoming the leader of packaging in the market.